The Unfulfilled Promise of Oil and Growth : Poverty, Inclusion and Welfare in Iraq 2007-2012 - World Bank (Washington, DC, 2015)
Iraq appears to have firmly entered the ranks of upper middle-income countries in 2012, having experienced strong economic growth following the establishment of a civilian elected government in 2005-06. In 2012 the years of growth culminated in a per capita GDP of 2472 constant 2005 US$. This three-volume poverty and inclusion assessment provides the first in-depth analysis of Iraq's economic and social development during the period of 2007 to 2012. Volume 1 is an overview of the economic climate in Iraq, providing brushstroke descriptions of its poverty reduction plans, labor markets, public health data, and education focal points. Volume 2 is a nine-chapter report on the years between 2007 and 2012, a period of relative stability in Iraq. 2007 marks the end of sectarian violence, which lasted until 2012, prior to the militancy and insurgency in the northern governorates of the summer of 2014. The country has been a nexus of conflict and fragility since the early 1980s, and has experienced multiple types of conflict: insurgency, international war, sectarian strife, persistent terrorism, regional fragmentation, and spillovers from conflict in other countries. What should have been a promising endowment of natural resources of land, oil and gas, as well of human capital, did not provide the foundation for poverty reduction and shared prosperity. The realization of potential was confounded by war and repression. A key priority of the Government of Iraq since 2005-06 has been to fill the huge knowledge gap in terms of a deeper understanding of the state of the economy and of a range of socioeconomic indicators of welfare with the objective of building a strong evidence base for effective policy making. The rich analyses presented in this report go well beyond counting the poor. It gives an incisive understanding of the multi-layered development challenges faced by the nation, which serves as a testament to the commitment of the Government of Iraq, the staff of the Central Statistics Office, and the Kurdistan Region Statistics Office. It will form the basis for a new strategy for Iraq's development and ensure broad-based welfare improvements for the population. Volume 3 consists of nine annexes and nine references in the forms of tables, boxes, and equations used in the methodologies.